2018
DOI: 10.5194/bg-15-2803-2018
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification increases the sensitivity of and variability in physiological responses of an intertidal limpet to thermal stress

Abstract: Abstract. Understanding physiological responses of organisms to warming and ocean acidification is the first step towards predicting the potential population- and community-level ecological impacts of these stressors. Increasingly, physiological plasticity is being recognized as important for organisms to adapt to the changing microclimates. Here, we evaluate the importance of physiological plasticity for coping with ocean acidification and elevated temperature, and its variability among individuals, of the in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The effects of sudden changes in the sea surface has been reported in several studies such as the high mortality of krill near Carlini Station, King George Island (Fuentes et al 2016) and the loss of ability to adapt to sudden changes in water such as in scallops (Adamussium colbecki), clams (L. elliptica) and limpets (N. concinna) (Peck 2005;Peck et al 2010), marine invertebrates (Odontaster validus and Paraceradocus gibber) (Clark et al 2008a, b, c), and sea urchins (S. neumayeri) (González-Aravena et al 2018). Moreover, the intertidal limpet, Cellana toreuma, showed a significant increase in Hsp70 expression for coping with ocean acidification and elevated temperature (Wang et al 2018). Yusof et al (2021) reported that the Antarctic yeast, G. antarctica, showed increasing expression of Hsp70s upon thermal stress.…”
Section: Hsp70 Expression Changes In Antarctic Organisms Exposed To Heat Salinity and Ph Stressorsmentioning
confidence: 99%
“…The effects of sudden changes in the sea surface has been reported in several studies such as the high mortality of krill near Carlini Station, King George Island (Fuentes et al 2016) and the loss of ability to adapt to sudden changes in water such as in scallops (Adamussium colbecki), clams (L. elliptica) and limpets (N. concinna) (Peck 2005;Peck et al 2010), marine invertebrates (Odontaster validus and Paraceradocus gibber) (Clark et al 2008a, b, c), and sea urchins (S. neumayeri) (González-Aravena et al 2018). Moreover, the intertidal limpet, Cellana toreuma, showed a significant increase in Hsp70 expression for coping with ocean acidification and elevated temperature (Wang et al 2018). Yusof et al (2021) reported that the Antarctic yeast, G. antarctica, showed increasing expression of Hsp70s upon thermal stress.…”
Section: Hsp70 Expression Changes In Antarctic Organisms Exposed To Heat Salinity and Ph Stressorsmentioning
confidence: 99%
“…Changes in body temperature are often among the most commonly studied responses for ectothermic marine invertebrates as temperature plays a large part in controlling cellular to physiological reactions, which in turn affects metabolism, growth and reproductive rates (Grigaltchik et al, 2012;Sinclair et al, 2016). Even small changes in the environment can cause a broad range of physiological responses due to variation among and within species (Harley et al, 2017;Wang et al, 2018). In particular, there has been an increasing focus on the physiological impacts of heatwaves, which are increasing in magnitude and frequency, increasing the likelihood that organisms are being subjected to thermal conditions beyond their optimal and lethal limits (Lannig et al, 2010;Sinclair et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Large variation in responses, even within a species, highlights that genetic variation and variability in physiological plasticity can affect the likelihood that populations survive short-term extremes (Wang et al, 2018). Should enough individuals be able to acclimate to novel conditions during extreme events, populations and communities may be able to handle future conditions better than currently predicted (Seebacher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term studies are important in order to avoid inaccurate assessments of the chronic effects of ocean acidification ( Kurihara et al, 2013 ; Moulin et al, 2015 ; Queirós et al, 2015 ; Riebesell and Gattuso, 2015 ; Lucey et al, 2016 ). Organisms living in coastal or upwelling environments currently experience highly fluctuating p CO 2 /pH on diurnal, tidal and seasonal cycles ( Hofmann et al, 2011 ; Wang et al, 2018 ). Therefore, local adaptation plays a crucial role in population sensitivity ( Hofmann et al, 2014 ; Vargas et al, 2017 ), and understanding long term tolerance in these organisms is important to an assessment of their response.…”
Section: Introductionmentioning
confidence: 99%